MENCIPTAKAN SISTEM DIGITALISASI PENGELOLAAN TRANSAKSI PADA USAHA COFFEE SHOP MELALUI PROGRAM WIRAUSAHA MERDEKA UNIVERSITAS MUHAMMADIYAH SURAKARTA 2023 - Putri Sholekhah, Ayu Mandira; Sari, Shinta Permata (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The Independent Entrepreneurship Program is an opportunity for students as agents of change to contribute in the form of developing creative and innovative business models. This Program is expected to improve the competence and employability of students, especially in business development. One of the businesses that is the attraction and attention in the 2023 independent entrepreneur program at the Univeritas Muhammadiyah Surakarta is the culinary business because this business field is very promising and becomes the basic need of every human being. In fact, in the culinary business most people do not equip themselves in the ability to manage transactions as happened to small and medium businesses in Lignum Coffee & Eatery. Observations and interviews with relevant parties have been conducted to obtain more in-depth information and documentation. The creation of a digital transaction management system by utilizing Microsoft Access software is a solution offered to Lignum Coffee & Eatery partners where the results of this system provide convenience in the process of inputting transactions, managing revenue, and providing an overview of the pace of business sales.